2020
DOI: 10.1002/mp.14006
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of multicontrast MR images through deep learning

Abstract: Purpose Magnetic resonance (MR) imaging with a long scan time can lead to degraded images due to patient motion, patient discomfort, and increased costs. For these reasons, the role of rapid MR imaging is important. In this study, we propose the joint reconstruction of multicontrast brain MR images from down‐sampled data to accelerate the data acquisition process using a novel deep‐learning network. Methods Twenty‐one healthy volunteers (female/male = 7/14, age = 26 ± 4 yr, range 22–35 yr) and 16 postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…This was achieved by allowing the gradient calculated from the FCN classification loss to propagate back to the generator to implicitly convey the disease-related information to the generator. As a result, the classification loss that was propagated provided a momentum for the generator to generate images that contributed to 16 [6,20] 16 [6,20] 16 [4,20] 16 [7,20] 16 [6,20] 14 [7,20] [24,30] 23.5 [18,28] 30 [26,30] 26 [24,30] 23 [20,27] 29 [20,30] 22 [0,30] 29 [25,30] 18 [6,22] Three independent datasets including (a) the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, (b) the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL), and (c) the National Alzheimer's Coordinating Center (NACC) were used for this study lower cross-entropy loss and thus facilitated better image classification. The generator of the GAN model consists of three 3D convolutional blocks in which each convolutional operation was followed by batch normalization and rectified linear unit (ReLu) activation.…”
Section: Deep Learning Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This was achieved by allowing the gradient calculated from the FCN classification loss to propagate back to the generator to implicitly convey the disease-related information to the generator. As a result, the classification loss that was propagated provided a momentum for the generator to generate images that contributed to 16 [6,20] 16 [6,20] 16 [4,20] 16 [7,20] 16 [6,20] 14 [7,20] [24,30] 23.5 [18,28] 30 [26,30] 26 [24,30] 23 [20,27] 29 [20,30] 22 [0,30] 29 [25,30] 18 [6,22] Three independent datasets including (a) the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, (b) the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL), and (c) the National Alzheimer's Coordinating Center (NACC) were used for this study lower cross-entropy loss and thus facilitated better image classification. The generator of the GAN model consists of three 3D convolutional blocks in which each convolutional operation was followed by batch normalization and rectified linear unit (ReLu) activation.…”
Section: Deep Learning Frameworkmentioning
confidence: 99%
“…Since its introduction, there has been a surge of interest in the application of GAN frameworks related to the brain. Some of the applications include image generation with improved properties such as achieving super resolution or better quality [6][7][8][9][10][11], data augmentation [12][13][14], segmentation [9,[13][14][15][16], image reconstruction [17][18][19][20], image-to-image translation [21][22][23][24], and motion correction [25,26]. While these important studies have demonstrated the exciting prospect of using GAN architectures, there is a limited amount of work that has focused on utilizing the generated images for subsequent tasks such as disease classification [27].…”
Section: Introductionmentioning
confidence: 99%
“…As the rapid growth of applying deep learning in MRI, [19][20][21] recently, deep learning-based end-to-end frameworks have been investigated for multimodal MR image synthesis. 13,[22][23][24][25][26][27][28][29][30][31][32] Especially, the achievable accuracy of synthesis has been highly improved with the superior image synthesis capability of generative adversarial networks (GANs). 33 These deep neural network-based methods can be grouped into three main categories depending on their input/output modalities: (a) single-input single-output (SISO), (b) multi-input singleoutput (MISO), (c) multi-input multi-output (MIMO).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the DL methods operate at the image-level [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] with the networks learning a mapping from aliased images, reconstructed from under-sampled k-spaces using the inverse Fourier transform, to de-aliased images. The de-aliased image can be the final product [23,25,27,24,31,32,35], be used as input of classic approaches [21] or be combined with the initial under-sampled k-space before a refinement step [26,28,34]. The network architecture can also be designed to mimic a classic iterative reconstruction where steps of reconstruction and DL-based regularization alternate [22,29,30,33].…”
Section: Image Reconstructionmentioning
confidence: 99%